A new anaxyelid sawfly (Insecta, Hymenoptera, Siricoidea) in mid-Cretaceous Myanmar amber. (May 2020) - Wang, Yimo; Wang, Mei; Rasnitsyn, A.P.; Shih, Chungkun; Ren, Dong; Kopylov, Dmitry S.; Gao, Taiping
Abstract: A new sawfly, Sclerosyntexis hirsuta gen. et sp. nov., in the subfamily Syntexinae of the Anaxyelidae is described from the mid-Cretaceous Myanmar (Burmese) amber. The new taxa is established primarily based on the following characters, i.e. body fusiform with a large head; antenna with pedicel almost twice as long as the first flagellomere; mesonotum with longitudinal, scuto-scutellar sulci; forewing with pterostigma completely sclerotized; Sc and 1r-rs absent; hind wing with cell r open distally; 1r-m longer than 1-Rs and 1-M; m-cu lost; free ending of Cu lost, 1-Cu and cu-a straight. Sclerosyntexis hirsuta gen. et sp. nov. has a short and oval body shape, which is unique in Anaxyelidae, since the bodies of most xylophagous anaxyelids are long and subcylindrical. The finding is the first record of Anaxyelidae in Myanmar amber hitherto, providing important morphological characters to enhance our understanding of the Anaxyelidae.